2006
DOI: 10.1055/s-2006-931542
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Repetitive Transcranial Magnetic Stimulation Improves Refractory Depression by Influencing Catecholamine and Brain-Derived Neurotrophic Factors

Abstract: These results suggest that rTMS treatment brings about some improvement in refractory depression, especially for symptoms such as agitation, by influencing MHPG and BDNF, which is in accordance with previous reports showing that BDNF was increased by various antidepressants treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 47 publications
4
71
1
Order By: Relevance
“…The effect of rTMS on BDNF levels in depressed subjects has received considerably greater attention because of the strong links between BDNF and the pathophysiology of depression (Krishnan and Nestler, 2008;Taliaz et al, 2010). In depressed patients who responded to TMS treatment, both high-frequency (Yukimasa et al, 2006;Zanardini et al, 2006) and low-frequency (Zanardini et al, 2006) rTMS were reported to increase BDNF serum levels; however, a different study reported no change induced by high-frequency rTMS (Lang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of rTMS on BDNF levels in depressed subjects has received considerably greater attention because of the strong links between BDNF and the pathophysiology of depression (Krishnan and Nestler, 2008;Taliaz et al, 2010). In depressed patients who responded to TMS treatment, both high-frequency (Yukimasa et al, 2006;Zanardini et al, 2006) and low-frequency (Zanardini et al, 2006) rTMS were reported to increase BDNF serum levels; however, a different study reported no change induced by high-frequency rTMS (Lang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Using standard figure-of-8 coils, two groups have found increased BDNF serum levels after high-frequency treatment [7,8] of depressed patients, but the same also observed increased BDNF levels following low-frequency treatment [8], and a third group found no effect on BDNF serum levels in response to high-frequency treatment of depression [14]. Many groups have focused on a connection between depression and BDNF concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A potential effect of rTMS on BDNF concentration in these diseases has been explored in previous studies [7,8]. The BDNF concentration in serum [9,10] or plasma [11] is decreased in depressed patients and may be associated with characteristics of neuroticism in healthy people [10], and antidepressant therapy has been suggested as potentially affecting BDNF concentration, mostly in the form of increasing peripheral blood concentrations [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma was quickly separated in a centrifuge and stored at À808C until assayed. The plasma HVA and MHPG levels were analyzed by HPLC-ECD according to the method described previously The plasma BDNF levels were measured using a BDNF Emax Immunoassay Kit (Promega, Madison, WI, USA) according to the method described previously (Yukimasa et al, 2006). The protocol of this study was approved by the Ethics Committee of the University of Occupational and Environmental Health.…”
Section: Methodsmentioning
confidence: 99%